Eksaminasi Khusus Kejaksaan Agung Dalam Perkara Tindak Pidana - Tahya, Rizky Imanuel; Toule, Elsa Rina Maya; Pattipawae, Dezonda Rosiana (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Special Examination is the process of conducting research and looking for certain case files that attract the attention of the media or other cases which, in the opinion of the leadership, need to be examined both for active cases and cases that have been handled by prosecutors or public prosecutors and which have obtained permanent legal force.Purposes of the Research: The purpose of this study is to find out and analyze the authority of the Attorney General's Office in taking over the prosecution of criminal cases from the Public Prosecutor's Office and to find out and analyze the application of special examinations conducted by the Attorney General's Office in accordance with the provisions of the Laws and Regulations. The type of research used is normative legal research with an analytical descriptive type which examines the findings from the literature review which are then analyzed into several chapters with a systematic flow.Results of the Research: The results of the research are that the Attorney General, who is the main public prosecutor in handling criminal cases, has the authority to delegate some of his rights to the public prosecutor in handling criminal cases in accordance with a mechanism that is in accordance with positive law.